Chorthippus parallelus and Wolbachia: Overlapping Orthopteroid and Bacterial Hybrid Zones - Martínez-Rodríguez, Paloma; Bella, José L. (Frontiers in Genetics, 2018)
Wolbachia is a well-known endosymbiotic, strictly cytoplasmic bacterium. It establishes complex cytonuclear relations that are not necessarily deleterious to its host, but that often result in reproductive alterations favouring bacterial transmission. Among these alterations, a common one is the cytoplasmic incompatibility (CI) that reduces the number of descendants in certain crosses between infected and non-infected individuals. This CI induced by Wolbachia appears in the hybrid zone that the grasshoppers Chorthippus parallelus parallelus and C. p. erythropus form in the Pyrenees: a reputed model in evolutionary biology. However, this cytonuclear incompatibility is the result of sophisticated processes of the co-divergence of the genomes of the bacterial strains and the host after generations of selection and coevolution. Here we show how these genome conflicts have resulted in a finely tuned adjustment of the bacterial strain to each pure orthopteroid taxon, and the striking appearance of another, newly identified recombinant Wolbachia strain that only occurs in hybrid grasshoppers. We propose the existence of two superimposed hybrid zones: one organised by the grasshoppers, which overlaps with a second, bacterial hybrid zone. The two hybrid zones counterbalance one another and have evolved together since the origin of the grasshopper’s hybrid zone.